Methodologies and formalisms of resonance energy transfer in biophysics. Application to membrane model systems - Luís M. S. Loura; Rodrigo F. M. de Almeida; Manuel Prieto (International Journal of Photoenergy)
The formalisms of resonance energy transfer (RET) to a distribution of acceptors are reviewed for several geometries relevant to membranes (planar, bilayer, multilayer) and random probe distribution. Models for nonrandom probe distribution (mean concentration model, phase separation model) are presented. Selected examples of quantitative applications of RET to these systems are described. It is illustrated how information about domain size, partition coefficients, phase composition, phase separation kinetics and bilayer aggregation can be obtained from time-resolved RET data.